6 - ‘Surviving like a Bird’: Livelihood Coping Strategies in an Informal Settlement of Windhoek, Namibia - Botes, Lucius; Endjala, Tuwilika (African Sociological Review, 2022)
Thisstudy was done to investigate different types of sustainable livelihoods in an informal settlement of Windhoek, Namibia, and to identify and describe the coping mechanisms of these households. The study used mixed research using descriptive and exploratory designs. Quantitative data was collected using questionnaires, while qualitative data was collected through in-depth interviews with seven heads of households. A sample of 150 households was randomly selected to allow representation of the population. The descriptive statistic approach wasusedintheanalysisofdata,usingtheStatisticalPackagefortheSocialScience(SSPSversion 23). Qualitative data analysis was done through thematic content analysis of transcribed data. Thestudy revealed that people migrate to the city in search of employment. Themost important factor for determining a positive lived experience in the informal settlement was whether a person has employment or not. Furthermore, a strong reciprocal social link between rural and urban areas has been f ound. The practice of residents in urban areas who send part of their remittance to rural areas has a positive spin-off on the rural economy, where the majority of migrants hail f rom. It was also established that rural households in the rural sending areas contributed agricultural produce to sustain the livelihoods of these urban informal dwellers. The most precarious and vulnerable group was singled headed unemployed elderly women, a clear indication of the gendered nature of poverty. Based on the study findin s, various types of livelihoods and coping strategies have been identified from the study, namely rural-urban food transfer, informal sector activities, social network and remittance.